2019
DOI: 10.3390/molecules24224092
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis, Molecular Modelling and Preliminary Competition Binding Studies of AM-DAN as a NMDA Receptor PCP-Site Fluorescent Ligand

Abstract: Excitotoxicity related to the dysfunction of the N-methyl-d-aspartate receptor (NMDAR) has been indicated to play an integral role in the pathophysiology of multiple disease states, including neurodegenerative disorders such as Parkinson’s disease. There is a notable gap in the market for novel NMDAR antagonists, however current methods to analyse potential antagonists rely on indirect measurements of calcium flux and hazardous radioligand binding assays. Recently, a fluorescent NMDAR ligand, N-adamantan-1-yl-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Dansyl-chloride (5-(dimethylamino)naphthalene-1-sulfonyl chloride) is a highly reactive nonfluorescent reagent that easily reacts with amines, yielding fluorescent derivatives; the reaction is widely used for amino-acids derivatization and many other detection techniques [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Dansyl-chloride (5-(dimethylamino)naphthalene-1-sulfonyl chloride) is a highly reactive nonfluorescent reagent that easily reacts with amines, yielding fluorescent derivatives; the reaction is widely used for amino-acids derivatization and many other detection techniques [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that amantadine and memantine (compound 8 ) bind to the phencyclidine (PCP) binding site of the NMDA receptor and exert pharmacological effects [ 29 , 30 , 31 ]. In addition, pharmacophore and quantitative structure–affinity relationship analyses showed the structural requirement for binding to the PCP binding site: an amine moiety with an aromatic ring or aliphatic hydrocarbon structure, such as an adamantane and cycloalkane skeleton [ 25 , 32 , 33 ]. These structural features are similar to those of the test compounds, which exhibited strong inhibitory effects on the amantadine transport system in this study ( Figure 1 and Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coelenterazine H, E and 400a were used as luciferase substrates and added to a final concentration of 4.2 μM in BRET buffer. The BRET signal was measured at room temperature after different time points (5,15,30,45, 60 min) with a Tecan Spark plate reader (Tecan). The luminescence signal was observed within the range of 430 to 470 nm for coelenterazine H and coelenterazine E, while the TAMRA fluorescence signal was detected in the 550 to 700 nm range.…”
Section: Nanobret Ligand-binding Assaymentioning
confidence: 99%